THE DEVELOPMENT OF LIVEWORKSHEETS AS INTERACTIVE INSTRUCTIONAL MEDIA FOR TEACHING READING EXPOSITION TEXT AT SENIOR HIGH SCHOOL - Angelina Christine Simanjuntak; Indah Tri Purwanti (International Journal of Educational Best Practices, 2025)
This research aimed to develop and validate Liveworksheets as interactive instructional media to support the teaching of reading analytical exposition texts in senior high school. The study was motivated by the limited use of interactive media in English reading and students' difficulties in understanding exposition texts, particularly due to the lack of engaging materials. This study used the Research and Development (R&D) method and adopted the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model and focused on analysis, Design, and Development for the instructional media. This research involved needs analysis through structured interviews and questionnaires with teachers and students, as well as curriculum analysis based on the Merdeka Curriculum. The product was designed using Canva and implemented in the Liveworksheets platform, incorporating multimedia elements like video, pictures, and interactive exercises. The media was validated by a media expert, material expert, and pedagogic expert. The result showed that the developed Liveworksheets were categorized as "very valid" with an average score above 3.25 based on validity criteria. This shown that Liveworksheets are effective and feasible for use as interactive instructional media in teaching analytical exposition texts. This study concludes that Liveworksheets can enhance students' engagement and improve learning outcomes in reading comprehension